Existence of Subharmonic Solutions for a Class of Second-Order p-Laplacian Systems with Impulsive Effects - Wen-Zhen Gong; Qiongfen Zhang; X. H. Tang (Journal of Applied Mathematics)
By using minimax methods in critical point theory, a new existence theorem of infinitely many periodic solutions is obtained for a class of second-order p-Laplacian systems with impulsive effects. Our result generalizes many known works in the literature.